2018
DOI: 10.1002/1878-0261.12192
|View full text |Cite
|
Sign up to set email alerts
|

PIM2 interacts with tristetraprolin and promotes breast cancer tumorigenesis

Abstract: Tristetraprolin (TTP) is an AU‐rich element‐binding protein that regulates mRNA stability and plays important roles in cancer. The mechanisms by which TTP is regulated in breast cancer are poorly understood. Using multiple biochemical approaches, we found that proviral insertion in murine lymphomas 2 (PIM2) is a novel binding partner of TTP. Interestingly, PIM2 decreased TTP protein levels independent of its kinase activity. PIM2 instead targeted TTP protein for degradation via the ubiquitin‐proteasome pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
(47 reference statements)
1
23
0
Order By: Relevance
“…The cells were seeded onto six-well plates at a concentration of 200 cells in 2 ml culture medium per well and cultured at 37 °C and 5% CO 2 for 12–14 days. Cells were fixed by 4% paraformaldehyde, and then treated with crystal violet staining solution, and cells were photographed [ 28 ]. For wound healing assay, cells were cultured in six-well plates till a monolayer was formed.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were seeded onto six-well plates at a concentration of 200 cells in 2 ml culture medium per well and cultured at 37 °C and 5% CO 2 for 12–14 days. Cells were fixed by 4% paraformaldehyde, and then treated with crystal violet staining solution, and cells were photographed [ 28 ]. For wound healing assay, cells were cultured in six-well plates till a monolayer was formed.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we used immunofluorescent staining to determine endogenous PIM2 was colocalized with endogenous FBP1 primarily in the nucleus but also slightly in the cytoplasm (Figure 1 F). To determine which domains of PIM2 and FBP1 are responsible for regulating this interaction, truncated constructs of the functional domains of PIM2 and FBP1 were made for further analysis (Figure 1 G and 1 I) 5 , 22 . Co-IP analyses suggested that the kinase domain of PIM2 (33-286aa) was associated with FBP1 (Figure 1 H).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, various special inhibitors, including JP11646, SMI-4a and SGI-1776, have been developed for PIM kinase activity and have been used for clinical treatment 19 - 21 . Recently, we found that PIM2 acts as an oncogene in breast cancer 15 , 17 , 22 , but the underlying mechanism of its oncogene function remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…ZFP36 was a downregulated gene in BC, and upregulation of ZFP36 inhibited transactivation of ERα, cell proliferation, as well as the capacity to form new tumors 18,30 . It was noted that circRNAs played critical functions during tumor progression by binding to miRs and miRs affected behaviors of malignant cells by regulating posttranscriptional gene expression 11,31 .…”
Section: Discussionmentioning
confidence: 99%
“…The bioinformatics website miR.org identified zinc finger protein 36 (ZFP36) as a target gene of miR‐182. As an AU‐rich element‐binding protein, ZFP36 was poorly expressed in BC, and low‐expressed ZFP36 was associated with poor patient survival 18 . Moreover, in BC, ZFP36 was reported to suppress cell proliferation in vitro and inhibit tumor growth in vivo by activating cell cycle arrest at the S phase 19 …”
Section: Introductionmentioning
confidence: 99%